2017
DOI: 10.1590/0001-3765201720150017
|View full text |Cite
|
Sign up to set email alerts
|

Screening of plant extracts and fractions on Aedes aegypti larvae found in the state of Mato Grosso do Sul (linnaeus, 1762) (culicidae)

Abstract: The constant use of chemical insecticides for Aedes aegypti control has caused resistance in the mosquito populations. Thus, the objective of this study was to analyze the larvicidal potential of extracts and fractions of plants on A. aegypti larvae. The analysis included sixty one extracts and twenty five fractions of fifty botanical species at concentrations of 0.25; 0.12; 0.06 to 0.03 mg mL -1 ; 4 replications and one negative control of dechlorinate water and 1% DMSO; and a positive control with rotenone. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
5

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 31 publications
0
9
0
5
Order By: Relevance
“…Jagajeevanram et al (2016) reported only 70% death of 4th instar larvae of Anopheles stephensi after 72 h exposure to 0.5 % concentration of C. amada rhizome methanol extract. Whereas, Porto et al (2017) tested larvicidal activity of several different plants at 0.5 mg/mL concentration against Aedes aegypti among which evaluation of larvicidal property of ethanolic extract of T. indica leaves was also included and showed no mortality at that concentration. Use of mixture of these two plant extracts which is first time reported as mosquitocidal agent in our experiment showed significant mortality at much lower concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Jagajeevanram et al (2016) reported only 70% death of 4th instar larvae of Anopheles stephensi after 72 h exposure to 0.5 % concentration of C. amada rhizome methanol extract. Whereas, Porto et al (2017) tested larvicidal activity of several different plants at 0.5 mg/mL concentration against Aedes aegypti among which evaluation of larvicidal property of ethanolic extract of T. indica leaves was also included and showed no mortality at that concentration. Use of mixture of these two plant extracts which is first time reported as mosquitocidal agent in our experiment showed significant mortality at much lower concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Table 3 describes larvicidal activities, while Table 4 describes adulticidal, pupicidal, ovicidal, repellent and oviposition activities. Piper species (Piperaceae) demonstrated LC 50 ranging from 2.23 to 567 µg/mL for L3 and L4 larval stages [106,109,110]. The most active species extracts were Piper longum L. (fruit ethanolic), followed by P. sarmentosum (entire plant ethanolic LC 50 4.06 µg/mL) and Piper ribesoides Wall.…”
Section: Organic/aqueous Extractsmentioning
confidence: 99%
“…Among the various larvicides used as A. aegypti controllers, those of fungicidal origin (Gomes et al, 2015), plant extracts (Porto et al, 2017), seaweed (Salvador-Neto et al, 2016), essential oils (Ferreira et al, 2015), and different species of bacteria, as they have a great capacity for multiplication and dispersion in the environment (Pontes, 2018).…”
Section: Aedes Aegypti Control Strategiesmentioning
confidence: 99%